2022
DOI: 10.1007/s11606-022-07540-2
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination, Mental Health and Behavioral Health During the COVID-19 Pandemic: a National Survey in the United States

Abstract: Background While hate crimes rose during the COVID-19 pandemic, few studies examined whether this pandemic-time racial discrimination has led to negative health consequences at the population level. Objective We examined whether experienced and perceived racial discrimination were associated with mental or behavioral health outcomes during the pandemic. Design In October 2020, we conducted a national survey with minorities oversampled that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…To date, only one study has assessed the impact of COVID-related discrimination on sleep among Asian adults [ 19 ]. A few other analyses have examined discrimination (COVID- and non-COVID-related) during the pandemic and sleep among Asian, Black/African American, and White adults [ 29 , 30 ]. All found that COVID-related discrimination was associated with sleep disturbances and shorter sleep time.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study has assessed the impact of COVID-related discrimination on sleep among Asian adults [ 19 ]. A few other analyses have examined discrimination (COVID- and non-COVID-related) during the pandemic and sleep among Asian, Black/African American, and White adults [ 29 , 30 ]. All found that COVID-related discrimination was associated with sleep disturbances and shorter sleep time.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results are consistent with other recent investigations using US and UK samples ( Bray et al, 2021 ; Czeisler et al, 2020 ; Fitzpatrick et al, 2020 ; Proto and Quintana-Domeque, 2021 ) which have documented disparities in psychological distress and suicidality among Black and other racial/ethnic groups compared to their White peers. Numerous studies have demonstrated that factors such as overt racial discrimination and racial microaggressions ( Paradies et al, 2015 ; Quinn et al, 2020 ; Rosario-Williams et al, 2022 ; Shi et al, 2022 ), socioeconomic inequalities ( Lo and Cheng, 2018 ; Williams, 2018 ), and medical mistrust ( Hammond, 2010 ; Powell et al, 2019 ) have contributed significantly to greater risks of suicidality, particularly among racial/ethnic minority groups in the United States. The substantially greater relative risk of suicidality among racial/ethnic minorities highlights the critical need of culturally responsive suicide prevention services for this population, particularly given that disparities in mental health by race/ethnicity in the United States have been demonstrated in the emerging COVID-19 literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population of the US, researchers have identified racial and ethnic disparities in mental health outcomes during the pandemic, including worsened outcomes of depression and anxiety among Black, Hispanic, and Asian adults when compared to White adults ( 24 ). A study found that those who have experienced racial discrimination in the US were at higher risk of psychological distress and increased unhealthy behaviors (e.g., smoking) than those who have not ( 25 ). Persistent systemic social inequities, the additional barriers minorities face when trying to access mental health care, disparities in food security that exacerbated during the pandemic, and the co-occurrence of racially motivated attacks (e.g., murders of minorities by the police) are also cited as reasons for the widening racial disparities in mental health outcomes observed during the pandemic ( 24 , 26 ).…”
Section: Introductionmentioning
confidence: 99%